2018
DOI: 10.21608/ejana.2018.43512
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of L-arginine on the Suprarenal Gland of Adult Male Albino Rats Subjected to Recurrent Acute Restraint Stress: A Histological and Immunohistochemical Study

Abstract: Background: The adrenal glands are small flattened glands closely applied to the upper pole of each kidney. The adrenal cortex consists of three layers that vary primarily in the arrangement of the secretory cells comprising each layer. The gland adapts to various forms of acute and chronic stress. Nitric oxide (NO) is an important endogenous biological modulator, produced by various cell types in different tissues and has diverse physiological actions, including the modulations of vascular resistance, tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…A statistically significant decrease of iNOS immunoreactivity in the GSE‐stress group compared to the stress group was well observed. (Table 1, Figures 3 and 8) Our results were in agreement with Abdel Malak & Amin, who demonstrated that acute restraint stress also caused a statistically highly significant increase in the distribution of iNOS in both cortex and medulla within nerve cells and nerve fibers compared to the control group (Abdel Malak & Amin, 2018). Duan et al, highlighted that decreased iNOS expression in the adrenal gland was associated with inhibition of iNOS‐related nitrative stress, nitric oxide (NO) production, and nitrotyrosine formation which might attribute to the protective effect of resveratrol against endotoxemia‐associated adrenal insufficiency (Duan et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…A statistically significant decrease of iNOS immunoreactivity in the GSE‐stress group compared to the stress group was well observed. (Table 1, Figures 3 and 8) Our results were in agreement with Abdel Malak & Amin, who demonstrated that acute restraint stress also caused a statistically highly significant increase in the distribution of iNOS in both cortex and medulla within nerve cells and nerve fibers compared to the control group (Abdel Malak & Amin, 2018). Duan et al, highlighted that decreased iNOS expression in the adrenal gland was associated with inhibition of iNOS‐related nitrative stress, nitric oxide (NO) production, and nitrotyrosine formation which might attribute to the protective effect of resveratrol against endotoxemia‐associated adrenal insufficiency (Duan et al, 2016).…”
Section: Discussionsupporting
confidence: 90%